THE INFLUENCE OF ORGANIZATIONAL COMMITMENT, WORK DISCIPLINE, AND WORK ENVIRONMENT FOR THE PERFORMANCE OF LOADING AND UNLOADING EMPLOYEES AT PT. MMP (MOROWALI MITRA PERKASA) CENTRAL SULAWESI - Khrisna, Gagas Pandu; Santoso, Bowo (Yayasan Education and Social Center, 2024)
This research is entitled The Influence of Organizational Commitment, Work Discipline, and Work Environment for the Performance of Loading and Unloading Employees at PT.MMP (Morowali Mitra Perkasa). Quantitative research is utilized in this approach to research, with employee performance as the dependent variable and organizational commitment, work discipline, and work environment as the independent variables. The population in this study were employees in the field, totaling 530 employees. The sample for this research was determined using a